2002
DOI: 10.1002/oti.164
|View full text |Cite
|
Sign up to set email alerts
|

The use of the QNST–II as a measure for the identification of children with perceptual‐motor deficits

Abstract: This study aimed to examine the ability of the Quick Neurological Screening Test QNST II) (Mutti et al., 1998) to discriminate between children with and without perceptual-motor deficits and to further clarify its psychometric characteristics. Ninety-four children aged six to seven years were tested on the QNST-II. Out of this pool of subjects, 63 children had perceptual-motor deficits and 31 were typical controls. The children with perceptual-motor deficits scored significantly lower than the control children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Another widely used test is the Quick Neurological Screening Test. Parush et al 31 have studied reliability and validity aspects of the Quick Neurological Screening Test. In their study, interrater reliability was 0.89 and test–retest reliability was 0.63, and therefore had comparable interrater and lower test–retest reliability than our results for the NSS examination.…”
Section: Discussionmentioning
confidence: 99%
“…Another widely used test is the Quick Neurological Screening Test. Parush et al 31 have studied reliability and validity aspects of the Quick Neurological Screening Test. In their study, interrater reliability was 0.89 and test–retest reliability was 0.63, and therefore had comparable interrater and lower test–retest reliability than our results for the NSS examination.…”
Section: Discussionmentioning
confidence: 99%
“…No other studies in PAE were found for comparison, although two studies were found in related populations. In one study the QNST‐2 discriminated between children ( n =94) with perceptual‐motor deficits (often reported in children with FASD) compared with children with typical development. In the second study, children ( n =23) with Developmental Coordination Disorder had a mean QNST‐2 Total Score within the ‘moderate discrepancy’ category (6th–24th centile) category.…”
Section: Discussionmentioning
confidence: 99%
“…This standardized, norm‐referenced instrument was chosen because it is recommended in FASD diagnostic guidelines and used in FASD clinics in North America. It is a well validated tool with high sensitivity (97%) and specificity (84%) that has been shown to be a useful screening tool strongly predictive of school performance and learning difficulty . The QNST‐2 comprises 15 tests (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation